PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP TELEPRESSURE PADA KARYAWAN MAGANG GENERASI Z DI LINGKUNGAN VIRTUAL - Fitriatul, Siti Fitriatul Zahroh; Widiasih, Puti Archianti (Psikologi UHAMKA, 2025)
Technological advances have shifted work communication systems, including the emergence of telepressure, which is pressure to respond quickly to virtual work messages. This study aims to determine the effect of transformational leadership style on telepressure in generation Z interns who work virtually. The study used a quantitative method with purposive sampling technique. Data were obtained from 152 respondents, but only 150 were analyzed according to the inclusion criteria. The instruments used were the Multifactor Leadership Questionnaire Scale (MLQ) developed by Bernard Bass and Bruce Avolio (1995) and the Workplace Telepressure Scale developed by Barber and Sanutzi (2015). The analysis technique used in this research is simple linear regression analysis technique. The results of the analysis showed a significant positive influence between transformational leadership style and telepressure (r = 0.032, P < 0.05). In addition, the regression results showed that transformational leadership style contributed 3.1% to telepressure. These findings indicate that the higher the transformational leadership style applied, the higher the telepressure experienced by interns.